220 Time to presentation of Peyronie's Disease in the era of injections and information. Issue 1 (1st April 2022) - Ly, L; Morales-Lopez, R; Metro, M
ABSTRACT: Introduction: Characterized by acquired fibrosis of the tunica albuginea, Peyronie's disease (PD) can cause penile curvature, pain, and plaque, as well as erectile dysfunction and difficulty with penetration. Using online surveys in 2007-2008, Dibenedetti et al found that the prevalence of PD in adult men in the US was 0.5% based on PD diagnosis; 0.8% based on PD diagnosis or treatment of PD; and 13.1% based on diagnosis, treatment, or any symptom of PD. They found that 68% of patients saw a doctor when they first noticed symptoms, at a mean time to see a doctor of 16.8 (SD = 5.5) months. The other third, or 32%, of patients who sought treatment later in the disease course, had a mean time of 46.2 (SD = 8.4) months. Only 5% of patients presented with current pain, thus in the active phase. Objective: Our study investigated how patient presentation for PD changed after two sentinel events: 1) the FDA approval of intralesional injections of collagenase clostridium histolyticum (CCH) in 2013, and 2) the national publicity surge for PD in 2016-2017. We then aimed to compare this data to a prior study by Dibenedetti et al conducted for patients in 2007-2008. Methods: Our retrospective, single institution study was conducted as a chart review of patients presenting from 2014 to 2020 with penile curvature, pain, or plaque. Descriptive statistics were used to compile data at the time of initial evaluation by the reconstructive urologist, including patient demographics, pre-treatment assessments, and time to evaluation. Results: Our study included 152 adult men, and mean age was 57.9 years old (SD = 8.1) (Table 1). Initial symptoms included penile curvature (87%), pain (30%), and plaque (8%). 38% of patients were in the active phase of PD at time of evaluation. The mean time from onset of symptoms to evaluation by the specialized urologist was 27.5 months (SD = 53.2, range 1 to 360 months) (Figure 1). For the 2/3 of patients, or 68%, who had the shortest time to evaluation, the mean duration of PD symptoms prior to evaluation by a specialized urologist was 10.0 months (SD = 4.6) (Figure 2). For the 1/3 of patients, or 32%, who had the longest time to evaluation, the mean duration of PD symptoms prior to evaluation was 69.7 months (SD = 80.6). Conclusions: Over the years, the majority of PD patients are presenting sooner in their PD course. The outlier patients, or those who have suffered from PD for a relatively long time, are also presenting for evaluation and treatment. These trends are likely influenced by the FDA approval of intralesional injections of CCH and by the national media efforts to raise awareness of the underdiagnosed and undertreated disease. Disclosure: No